Niclosamide suppresses macrophage-induced inflammation in endometriosis. Issue 5 (17th January 2020) - Sekulovski, Nikola; Whorton, Allison E; Tanaka, Tomoki; Hirota, Yasushi; Shi, Mingxin; MacLean, James A; de Mola, Julio Ricardo Loret; Groesch, Kathleen; Diaz-Sylvester, Paula; Wilson, Teresa; Hayashi, Kanako
Abstract: Endometriosis is a common gynecological disease, which causes chronic pelvic pain and infertility in women of reproductive age. Due to limited efficacy of current treatment options, a critical need exists to develop new and effective treatments for endometriosis. Niclosamide is an efficacious and FDA-approved drug for the treatment of helminthosis in humans that has been used for decades. We have reported that niclosamide reduces growth and progression of endometriosis-like lesions via targeting STAT3 and NFĸB signaling in a mouse model of endometriosis. To examine the effects of niclosamide on macrophage-induced inflammation in endometriosis, a total of 29 stage III–IV endometrioma samples were used to isolate human endometriotic stromal cells (hESCs). M1 or M2 macrophages were isolated and differentiated from fresh human peripheral blood samples. Then, hESCs were cultured in conditioned media (CM) from macrophages with/without niclosamide. Niclosamide dose dependently reduced cell viability and the activity of STAT3 and NFκB signaling in hESCs. While macrophage CM stimulated cell viability in hESCs, niclosamide inhibited this stimulation. Macrophage CM stimulated the secretion of proinflammatory cytokines and chemokines from hESCs. Most of these secreted factors were inhibited by niclosamide. These results indicate that niclosamide is able to reduce macrophage-induced cell viability and cytokine/chemokine secretion in hESCs by inhibiting inflammatory mechanisms via STAT3 and/or NFκB signaling. Abstract : Niclosamide is able to inhibit the inflammatory mechanisms in primary endometriotic stromal cells stimulated by macrophages via STAT3 and NFκB signaling.